Analysis Dimension of Healthy Work Environment for Successful Patient Safety Incident Reporting: A Cross Sectional Study - Surya Hadi Arsani; Ahsan; Fransiska Imavike Fevriasanty (Universitas Muhammadiyah Yogyakarta, 2023)
Incident reporting of patient safety is the first step in improving patient safety through learning from previous incidents. However, barriers to incident reporting caused by work environment factors make the patient safety incident system not run well in various countries. This study analyzes nurses’ dimensions of a healthy work environment toward reporting patient safety incidents. This study used an observational analytic design with a cross-sectional approach. This study was conducted in a regional hospital in West Nusa Tenggara province in October - November 2022 with a total sample of 151 nurses working in the inpatient room. Sample determination used a quota sampling technique. Measurement of a healthy work environment was adopted from the HWE Tools and Measurement of incident reporting. The questionnaire was adopted from the Patient Safety Incident Reporting and Learning Systems. Data collection techniques implemented primary data questionnaires and multiple linear regression tests. The results showed a relationship between communication, collaboration, decision-making, staff suitability, recognition, and leadership to patient safety incident reporting with a p-value of 0.001 each (p <0.05). The most dominant relationship is Recognition (B=0.39, p=0.001). Recognition means stimulating a person’s psychological growth and a positive mindset to complete tasks, solve problems, overcome obstacles, and bounce back from difficult situations. Therefore, individual attitudes alone are not enough to make individuals behave to report or not report incidents but must be supported by the wishes of those who have great influence in the environment and want individuals to report if an incident occurs.